Pengaruh Pengungkapan Manajemen Risiko terhadap Nilai Perbankan yang Terdaftar di BEI Tahun 2020-2024 - Muhammad Islah Syafi’i (AKUNTANSI 45, 2026)
This study analyzes the effect of risk management disclosure on the firm value of banks listed on the Indonesia Stock Exchange for the 2020-2024 period. Data were collected from the annual reports and sustainability reports of seven banks selected using purposive sampling method. Risk management disclosure was measured based on the implementation of Enterprise Risk Management (ERM), while firm value was measured using Tobin's Q. The results of linear regression analysis show that risk management disclosure does not significantly affect firm value. This finding suggests that investors may pay more attention to other fundamental factors than risk management information when valuing companies. These findings indicate that investors may be paying more attention to other fundamental factors than risk management information when assessing companies. This also highlights the need for companies to improve transparency and communication regarding risk management strategies to ensure greater investor awareness. Furthermore, this study recommends that regulators encourage more consistent risk reporting standards in the banking sector. Future research could expand the sample and consider external factors such as macroeconomic conditions or market sentiment to examine the impact of risk disclosure more comprehensively.